2003
DOI: 10.1271/bbb.67.1767
|View full text |Cite
|
Sign up to set email alerts
|

RNase ES ofStreptomyces coelicolorA3(2) Can Complement therneandrngMutations inEscherichia coli

Abstract: The Streptomyces coelicolor gene SCC88.10c encodes a protein (RNase ES) which is homologous to endoribonucleases in the RNase E/G family. We expressed S. coelicolor RNase ES as a 6 x His-tagged protein in an Escherichia coli mutant carrying a rng (which encodes RNase G) or a rne (which encodes RNase E) mutation to study whether S. coelicolor RNase ES is able to complement these mutations in host E. coli cells. The results clearly indicated that the S. coelicolor RNase ES can partially abrogate either the rng::… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Bottom, instability of psbA mRNA under darkness is caused post-transcription by RNases, which act on the AUbox (and SD) as targets. Scissor, endoribonuclease RNase E/G; packman, possible exoribonuclease larly, a Type III RNase E/G homologue of a Gram-positive bacterium, Streptomyces coelicolor A3(2), can also fulWll the functions of E. coli RNase E and RNase G (Inagawa et al 2003). Furthermore, a similar result was reported for the Type IV RNase E/G homologue of Aquifex aeolicus (Kaberdin and Bizebard 2005).…”
Section: Activity Domains Of Slr1129mentioning
confidence: 60%
“…Bottom, instability of psbA mRNA under darkness is caused post-transcription by RNases, which act on the AUbox (and SD) as targets. Scissor, endoribonuclease RNase E/G; packman, possible exoribonuclease larly, a Type III RNase E/G homologue of a Gram-positive bacterium, Streptomyces coelicolor A3(2), can also fulWll the functions of E. coli RNase E and RNase G (Inagawa et al 2003). Furthermore, a similar result was reported for the Type IV RNase E/G homologue of Aquifex aeolicus (Kaberdin and Bizebard 2005).…”
Section: Activity Domains Of Slr1129mentioning
confidence: 60%
“…It has also been reported that overproduction of the S. coelicolor RNase ES caused a severe growth defect in E. coli. 29) It is noteworthy that the expression patterns of cellular proteins changed drastically upon the expression of FL-NCgl2281 (Fig. 4).…”
Section: Discussionmentioning
confidence: 97%
“…37) These two studies suggest that the mycobacterial RNase E/G is functionally related to E. coli RNase E. S. coelicolor also has one RNase E/G homolog, which complemented both the E. coli rne-1 and the rng::cat mutation. 29,30) Bacillus subtilis has no RNase E/G homolog. It has RNase J instead.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations